Structure Sensitivity of Formic Acid Electrooxidation on Transition Metal Surfaces: A First-Principles Study. Issue 15 (1st January 2018) - Elnabawy, Ahmed O.; Herron, Jeffrey A.; Scaranto, Jessica; Mavrikakis, Manos
Abstract : Formic acid presents several advantages for use as a fuel in fuel cells. We present a first-principles based analysis of electrooxidation trends for formic acid on the close-packed facets of eight fcc metals: Au, Ag, Cu, Pt, Pd, Ni, Ir, and Rh, and four hcp metals: Co, Os, Ru, and Re. To explore the structure sensitivity of this reaction on the fcc metals, we also studied the open (100) facet of these eight metals. We find that the open facets of Au, Ag, Cu, Pt, and Pd are more energy-efficient (i.e. require less overpotential) for formic acid electrooxidation when compared to their close-packed facets. The opposite is true for the stronger-binding metals: Ni, Ir, and Rh. Using the free energy of adsorbed CO * and OH * as reactivity descriptors, we cast the thermochemistry of the reaction network into phase diagrams showing regions of rate-determining steps, together with their calculated free energies. This allows the identification of bimetallic alloys, potentially possessing improved electrocatalysis for formic acid electrooxidation, compared to Pt or Pd. We discuss the need for anode catalysts for direct formic acid fuel cells (DFAFCs) to diminish CO * poisoning, by promoting the formation of formate instead of carboxyl intermediate.